Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Numbered Head Together dipadu Contextual Teaching and Learning Terhadap Hasil Belajar Siswa SMA Imanuel Palu - Yulinda, Lika; Mustapa, Kasmudin; Ratman, Ratman (Jurnal Akademika Kimia, 2018)
This study aim was to determine the influence of application of cooperative learning model type numbered head together combination with contextual teaching and learning toward learning outcomes of students in SMA Imanuel Palu. This study used quasi experimental design with non randomized pretest-posttest control group. Sample used were two classes, Xb (n=30) as experimental and Xa (n = 30) as control one. The test of student learning outcomes data used the t-test statistical analysis of the two parties. The results of data analysis obtained, the average score of experimental class () was 50.50 with a standard deviation of 9.79 and for control class () was 41.03 with a standard deviation of 11.01. The result of testing hypothesis with the statistical t-test of two parties obtained that –ttable < tcalculation > +ttable (tcalculation = 2.35 and ttable = 2.00) with a significance level α= 0.05 and 58 degrees of freedom, then H0 was rejected and Ha was accepted. The result of the data analysis showed that there was any in learning outcomes between students in experimental class and the control class, until concluded there is any influences of application of cooperative learning model type numbered head together combination with contextual teaching and learning toward learning outcomes of students in SMA Imanuel Palu.